Mapping the landscape of sustainability literacy research in the Indonesian technical and vocational education - Ihsan, Fatihul; Himawanto, Dwi Aries; Suharno, Suharno (Journal of Education and Learning (EduLearn), 2025)
Technical and vocational education (TVE) in a country cannot only talk about a narrow scope in the world of education and work but also play a role in ensuring someone achieves a prosperous life socially, economically and environmentally without forgetting preparation for the next generation. This research will visualize and map the development trend of publications on sustainable development in the TVE scope worldwide and in Indonesia. The method used is descriptive quantitative and bibliometric analysis with research data taken from the Scopus database. The results of the study show that increasing research is essential for the development and efforts of the TVE community to increase the achievement of sustainable development goals (SDGs). Indonesia is recorded as having only started publication in 2017, with a total publication of 42 documents until early 2024. Interestingly, there has been a decline in the number of publications in the last two years. The results of the bibliometric analysis show that research topics in Indonesia have not yet demonstrated success in linking them to the social, economic and environmental spheres. Further research is recommended to conduct a systematic literature review to identify global action program (GAPs) in sustainable development research in TVE communities.